Bortezomib-Induced Bronchiolitis Obliterans Organizing Pneumonia - E. Vandeix; F. Favard; N. Pichon; M. Delage-Corre; B. Melloni; M. Clavel (Case Reports in Pulmonology)
Introduction. Bortezomib is a proteasome inhibitor indicated for the treatment of multiple myeloma patients. The most frequent side effects are gastrointestinal and neurological. Serious pulmonary complications have been described rarely. Observation. This case involves a 74-year-old man suffering from IgG Kappa myeloma treated with bortezomib, melphalan, and dexamethasone. After administering chemotherapy, the patient developed an acute respiratory distress syndrome (ARDS). A surgical pulmonary biopsy proved the existence of bronchiolitis obliterans organizing pneumonia (BOOP) lesions. Systemic corticotherapy led to a rapid improvement in the patient’s condition. Conclusion. This is the first reported histologically confirmed case of bortezomid-induced BOOP. Faced with severe respiratory symptoms in the absence of other etiologies, complications due to bortezomid treatment should be evoked and corticotherapy considered.